Respiratory symptoms and radiological findings in post-acute COVID-19 syndrome - Etienne-Marie Jutant; Olivier Meyrignac; Antoine Beurnier; Xavier Jaïs; Tai Pham; Luc Morin; Athénaïs Boucly; Sophie Bulifon; Samy Figueiredo; Anatole Harrois; Mitja Jevnikar; Nicolas Noël; et al. (ERJ Open Research, 2022)
Rationale The characteristics of patients with respiratory complaints and/or lung radiologic abnormalities after hospitalisation for coronavirus disease 2019 (COVID-19) are unknown. The objectives were to determine their characteristics and the relationships between dyspnoea, radiologic abnormalities and functional impairment. Methods In the COMEBAC (Consultation Multi-Expertise de Bicêtre Après COVID-19) cohort study, 478 hospital survivors were evaluated by telephone 4 months after hospital discharge, and 177 who had been hospitalised in an intensive care unit (ICU) or presented relevant symptoms underwent an ambulatory evaluation. New-onset dyspnoea and cough were evaluated, and the results of pulmonary function tests and high-resolution computed tomography of the chest were collected. Results Among the 478 patients, 78 (16.3%) reported new-onset dyspnoea, and 23 (4.8%) new-onset cough. The patients with new-onset dyspnoea were younger (56.1±12.3 versus 61.9±16.6 years), had more severe COVID-19 (ICU admission 56.4% versus 24.5%) and more frequent pulmonary embolism (18.0% versus 6.8%) (all p≤0.001) than patients without dyspnoea. Among the patients reassessed at the ambulatory care visit, the prevalence of fibrotic lung lesions was 19.3%, with extent <25% in 97% of the patients. The patients with fibrotic lesions were older (61±11 versus 56±14 years, p=0.03), more frequently managed in an ICU (87.9 versus 47.4%, p<0.001), had lower total lung capacity (74.1±13.7 versus 84.9±14.8% pred, p<0.001) and diffusing capacity of the lung for carbon monoxide (DLCO) (73.3±17.9 versus 89.7±22.8% pred, p<0.001). The combination of new-onset dyspnoea, fibrotic lesions and DLCO <70% pred was observed in eight out of 478 patients. Conclusions New-onset dyspnoea and mild fibrotic lesions were frequent at 4 months, but the association of new-onset dyspnoea, fibrotic lesions and low DLCO was rare.